Prevalence of Malnutrition Among Under Five Children Attending Primary Health Centers in Obio Akpor Local Government Area, Rivers State - Model Efai-vie Osuamkpe (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Malnutrition remains one of the most devastating threats to child survival and development, significantly increasing morbidity, impairing cognitive growth, and contributing substantially to under-five mortality worldwide. Nutrition is crucial to a child's growth and development in mainly, the first two years of life, which are seen as the window of opportunity for a child's wellbeing to be improved. Objective: This study assessed the prevalence of malnutrition among under-five children seeking health care in Primary health centers in Obio Akpor local government area, Rivers State. Methods: A cross-sectional study was conducted among children under five years of age attending primary healthcare centers between January and March 2025. A sample size of 281 participants was determined and selected using a simple random sampling technique. Data were collected using a structured questionnaire, which demonstrated acceptable internal consistency with a reliability coefficient of 0.71, as determined by Cronbach’s alpha. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS), version 27.0, and WHO Anthro software. Descriptive and inferential statistics including percentages, means, standard deviations, and chi-square tests were employed, with the level of significance set at 0.05. Results: The results showed that 199(72.9%) had normal weight, 39(14.3%) were underweight, 35(12.8%) were stunted, 18(6.6%) had severe acute malnutrition, 33(12.1%) were wasted and 5(20.1%) were at risk of malnutrition. The results also showed that 96(35.2%) of the children who were at risk of acute malnutrition were within the age of 6-11 months. Conclusion: It was concluded that, malnutrition is rife among under five children in Primary health centers in Obio Akpor Local Government Area of Rivers State. The Rivers State Primary Health Care Board should enforce regular checking of MUAC readings in every health centre to ensure early detection of malnutrition. Parents and caregivers should be sensitized on the importance of balanced, nutritious diets even with limited resources, when they visit health centers. Government should prioritize social protection programs such as food subsidies and community food banks to combat food insecurity. Gender-sensitive nutritional interventions should be promoted.